The proposed Ministry of Health - Davies, Margaret Llewelyn, 1861-1944 ; Phillips, Marion, 1881-1932 ; Webb, Emily; MacArthur, Mary R. (Mary Reid), 1880-1921
1918 1918 1910s 2 pages STANDING JOINT COMMITTEE of INDUSTRIAL WOMEN'S ORGANISATIONS Chairman : Vice-Chairman : Secretary : Miss MARY MACARTHUR Miss LLEWELYN DAVIES. Dr. MARION PHILLIPS The Proposed Ministry of Health. The undersigned, representing over 300,000 organised working women, desire to express the urgent need for the formation of a Ministry of Health at the earliest possible date, in order that effective action may be taken in regard to the pressing health problems arising out of the war, and particularly those connected with the Care of Mothers and Infants. Proposals of the Insurance Organisations. We are of opinion that the proposals put forward by the National Insurance organisations, in their Bill for the Establishment of a Ministry of Health, do not conform to the public interest, seeing that— (1) They complicate local machinery by multiplying authorities. (2) They allow Maternity and Infancy work to be entrusted to Insurance Committees, which have neither the machinery to deal with it, nor the confidence of married women — who have no voice in their control. (3) They perpetuate the system of representation of "interests" in the Central Authority, thus opening the door to the dominating influence of the Life Insurance Companies. Attitude of the Local Government Board. We regard the Public Health Services as the essential foundation of a Ministry of Health, but consider that they must be entirely dissociated from the Poor Law in any proposals that are likely to meet with the support of the workers. The reference of the whole matter to a Royal Commission would involve far too great a delay and is wholly unnecessary, and, in view of the urgency of securing legislation, we strongly oppose any such suggestion. Recommendations. We therefore make the following recommendations :— 1. That the Government should immediately introduce a Bill to establish a new Ministry of Health, which should be marked by the following characteristics:— (1) The inclusion in the Ministry of (a) all the health functions, including housing, of the Local Government Board which would entail the complete transformation of the Poor Law, the health side of it becoming part of the Public Health Services administered under Public Health, and not Poor Law Acts; (b) the Insurance Commission. 36/H24/3